Mitochondrial Complex I superoxide production is attenuated by uncoupling - Dlasková, Andrea; Hlavatá, Lydie; Jezek, Jan; Jezek, Petr (The international journal of biochemistry & cell biology, 2008)
Complex I, i.e. proton-pumping NADH:quinone oxidoreductase, is an essential component of the mitochondrial respiratory chain but produces superoxide as a side-reaction. However, conditions for maximum superoxide production or its attenuation are not well understood. Unlike for Complex III, it has not been clear whether a Complex I-derived superoxide generation at forward electron transport is sensitive to membrane potential or protonmotive force. In order to investigate this, we used Amplex Red for H(2)O(2) monitoring, assessing the total mitochondrial superoxide production in isolated rat liver mitochondria respiring at state 4 as well as at state 3, namely with exclusive Complex I substrates or with Complex I substrates plus succinate. We have shown for the first time, that uncoupling diminishes rotenone-induced H(2)O(2) production also in state 3, while similar attenuation was observed in state 4. Moreover, we have found that 5-(N-ethyl-N-isopropyl) amiloride is a real inhibitor of Complex I H(+) pumping (IC(50) of 27 microM) without affecting respiration. It also partially prevented suppression by FCCP of rotenone-induced H(2)O(2) production with Complex I substrates alone (glutamate and malate), but nearly completely with Complexes I and II substrates. Sole 5-(N-ethyl-N-isopropyl) amiloride alone suppressed 20% and 30% of total H(2)O(2) production, respectively, under these conditions. Our data suggest that Complex I mitochondrial superoxide production can be attenuated by uncoupling, which means by acceleration of Complex I H(+) pumping due to the respiratory control. However, when this acceleration is prevented by 5-(N-ethyl-N-isopropyl) amiloride inhibition, no attenuation of superoxide production takes place.
Keywords: protonové pumpy; kyselina jantarová; maláty; Uncoupling Agents; buněčné dýchání; superoxidy; Mitochondria, Liver; Proton Pumps; Dose-Response Relationship, Drug; Models, Biological; Glutamic Acid; Succinic Acid; Superoxides; krysa rodu Rattus; rozpřahující látky; zvířata; amilorid; potkani Wistar; jaterní mitochondrie; Rats, Wistar; peroxid vodíku; Electron Transport Complex I; biologické modely; Rats; Amiloride; respirační komplex I; vztah mezi dávkou a účinkem léčiva; Animals; Malates; Hydrogen Peroxide; kyselina glutamová; Cell Respiration